2017
DOI: 10.1590/1414-431x20176390
|View full text |Cite
|
Sign up to set email alerts
|

Two novel Co(II) complexes with two different Schiff bases: inhibiting growth of human skin cancer cells

Abstract: Using two flexible Schiff bases, H2L1 and H2L2, two new cobalt II (Co(II))-coordination compounds, namely, Py3CoL1 (1) and Py3CoL2 (2) (Py=pyridine, L1=3,5-ClC6H2(O)C=NC6H3(O)-4-NO2, L2=3,5-BrC6H2(O)C=NC6H3(O)-4-NO2) have been synthesized under solvothermal conditions. Single crystal X-ray structural analysis revealed that compounds 1 and 2 are both six-coordinate in a distorted octahedral geometry, and the 1D chain structure was formed by the π…π and C-H…O interactions or C-H…Cl interaction. The in vitro anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 10 publications
(12 reference statements)
0
5
0
Order By: Relevance
“…Xiao et al [129] have reported Co (II) complexes with the two flexible Schiff base ligands of type Py 3 CoL 1 (113) and Py 3 CoL 2 (114) (where, Py ¼ Pyridine, L 1 ¼ 3,5-ClC 6 130e134]. Gambino et al [130] have reported the bioactive gallium complexes with tridentate substituted salicylaldehyde semicarbazone of the type [Ga III (LeH) 2 ](NO 3 ) (115e119) (Scheme 26) and have investigated for their antitumor activity.…”
Section: Antitumor Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Xiao et al [129] have reported Co (II) complexes with the two flexible Schiff base ligands of type Py 3 CoL 1 (113) and Py 3 CoL 2 (114) (where, Py ¼ Pyridine, L 1 ¼ 3,5-ClC 6 130e134]. Gambino et al [130] have reported the bioactive gallium complexes with tridentate substituted salicylaldehyde semicarbazone of the type [Ga III (LeH) 2 ](NO 3 ) (115e119) (Scheme 26) and have investigated for their antitumor activity.…”
Section: Antitumor Activitymentioning
confidence: 99%
“…Structure of 2,6-diacetylpyridine bis-4-phenyl-3-thiosemicarbazone(129). Structure of 2,6-diacetylpyridine bis-4-phenyl-3-thiosemicarbazone(129).…”
mentioning
confidence: 99%
“…Pyridine based cobalt metal complex were synthesized and characterized by Xiao et al [15]. The pyridine-metal complex ( cell lines in comparison to their corresponding organic ligand [15].…”
Section: Introductionmentioning
confidence: 99%
“…The in vitro cancer studies of all the compounds were assessed for their anti-proliferation test against a panel of selected human cancer cell lines such as HOP62 (lung) and BT 474 (breast) by using SRB (sulforhodamine B) assay [28][29][30][31][32][33][34][35][36][37] concentration of drug used 10, 20, 40, and 80 μg/mL ADR (adrimycin) was used as a positive control which controls cells with definite structure and clear cell wall without degeneration. Each drug was assayed inducing 50% growth inhibition (GI 50 ), total growth inhibition (TGI), and 50% cytotoxicity (LC 50 ) after a 48 h incubation period were calculated by linear interpolation from the observed data points.…”
Section: Methodsmentioning
confidence: 99%